Regularity and normality in ideal bitopological spaces (2021)
We introduce, and study, the regularity and normality in ideal bitopological spaces, absent subject in literature. Our definitions have the advantage of using only the open sets of the two underlying topologies. These new concepts represent generalizations of Kelly's concepts of pairwise regularity and pairwise normality. The extension of the T 0 , T 1 and T 2 axioms to these spaces is due to Caldas et al.